2017
DOI: 10.1155/2017/8310275
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antimicrobial Activities ofPogostemon cablin(Blanco) Benth.

Abstract: Pogostemon cablin (Lamiaceae) has been widely used in traditional medicine. In this study, the antioxidant and antimicrobial activities of leaves from P. cablin extracts were investigated. The water extracts had the highest total phenolic content 116.88±0.48 mg gallic acid equivalent/g of dry plant extract. Nevertheless, high levels of total flavonoid content were found in ethanolic extracts 280.12 ± 2.04 mg quercetin equivalent/g of dry plant extract. The highest antioxidant activities were found for the etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…This result was consistent with that of a previous study, which reported that the ethanolic P. cablin extract exhibited a noncytotoxic effect, with more than 70% cell viability. 39 The selection of the extract with the best antimalarial activity in an animal model that is widely used to predict drug activity was based on the greatest antimalarial activity and the lowest toxicity. According to the results of in vitro studies, the ethanolic P. cablin extract exhibited better antimalarial activity against the P. falciparum K1 strain and had no toxicity toward Vero cells.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with that of a previous study, which reported that the ethanolic P. cablin extract exhibited a noncytotoxic effect, with more than 70% cell viability. 39 The selection of the extract with the best antimalarial activity in an animal model that is widely used to predict drug activity was based on the greatest antimalarial activity and the lowest toxicity. According to the results of in vitro studies, the ethanolic P. cablin extract exhibited better antimalarial activity against the P. falciparum K1 strain and had no toxicity toward Vero cells.…”
Section: Discussionmentioning
confidence: 99%
“…Patchouli is a traditional Chinese medicine for the treatment of gastrointestinal symptoms. PEO and its derived compounds PA, PO, and β-PAE are the main active ingredients of patchouli that possess anti-inflammation, anti-oxidant, anti-microbial, anti-allergy, and anti-cancer effects based on the cellular and animal studies (Li et al, 2011; He et al, 2013; Jeong et al, 2013; Dechayont et al, 2017). It is our interest to investigate whether the commensal GM plays a role in the health benefits of patchouli.…”
Section: Discussionmentioning
confidence: 99%
“…These components of PC exhibited common as well as unique pharmaceutical activities (Li et al, 2014; Zhang et al, 2016a; Zhang et al, 2016b). For example, reports showed that PEO, PA, PO, and β-PAE possessed anti-inflammation, anti-oxidant, anti-cancer, immunomodulation in cellular and animal studies (Li et al, 2011; Liao et al, 2013; Jeong et al, 2013; Dechayont et al, 2017). Studies also showed that PEO, PA, and PO can suppress the growth of methicillin-resistant Staphylococcus aureus , Escherichia coli , and Helicobacterium both in vitro and in vivo experiments (Peng et al, 2014; Xie et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Along with the good number widely used procedures for measurement of antioxidant activity capacity, the DPPH radical scavenging analysis is one of the top known, correct, and regularly employed to measure the electron donating ability of the plant [12,13]. Dechayont et al, reported that the moderate antioxidant activity from Pogostemon cablin and inhibited bacteria commonly responsible for community and hospital acquired infections [14]. Usmangani et al reported that leaf and fruit extracts of D. palmatus were determined to have a certain level of radical scavenging effect, proportional to their level of phytochemicals [15].…”
Section: Resultsmentioning
confidence: 99%